Northwell intracoronary brachytherapy for the treatment of recurrent drug eluting stent in‐stent restenosis (NITDI study group). Issue 1 (13th January 2020) - Meraj, Perwaiz M.; Patel, Krunalkumar; Patel, Amitkumar; Doshi, Rajkumar; Srinivas, Guruprasad; Jauhar, Rajiv; Kaplan, Barry; Garzon, Ruby; Sharma, Anurag; Cao, Yijian; Diaz Molina, Ferney; Sharma, Rajiv
Abstract: Objective: The purpose of this study is to report on safety, short‐term and long‐term clinical efficacy following intracoronary brachytherapy (ICBT) for restenosis (ISR) in patients with drug eluting stents (DES). Background: ICBT is an effective treatment for ISR of bare metal stents (BMS) but its utilization has waned due to the advent of DES. ISR following DES occurs at a frequency of 8% or greater. Method: A retrospective analysis was performed on patients treated on an institutional review board (IRB) approved protocol using ICBT for DES ISR between January 2011 and October 2016. All patients were followed for 24 months for procedural complications, mortality, clinical ISR/target lesion revascularization (TLR) and stroke. Results: A total of 290 patients were identified with a mean age of 66.6 years. All of them had high rates of typical coronary artery disease risk factors. Our primary outcome, composite of in‐hospital mortality, myocardial infarction (MI), safety outcomes and procedural failure was noted in 1(0.3%) patient who had a MI. No other secondary outcome was noted in‐hospital. At 1‐year follow up, 12.4% patients had ISR, 1.7% patients died, and 1 (0.3%) had ischemic stroke. At 2‐year, 14.7% had ISR, and total 6 (2.1%) patients had MI. Conclusion: ICBT demonstrates excellent technical success rates for treatment, safety, and reasonable efficacy over 2‐years to be free from recurrent clinical ISR. This study represents the largest ICBT data for DES ISR to date among very complex lesion subsets, however, more prospective data will be needed to determine the optimal patient for treatment.